PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, AKTIVITAS, MARKET VALUE RATIO, UMUR, JAMNAN, DAN REPUTASI TRUSTEE TERHADAP PERINGKAT OBLIGASI (Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia 2012-2015) - Muhammad Prayogi, 13.05.52.0173; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of firm size, leverage, profitability, activity, market value ratio, age of bond, guarantee, trustee reputation to bond rating. This research is conducted in Bursa Efek Indonesia by using unit of analysis of non financial company. This sampling method using purposive sampling with research period of 2012 until 2015. The relationship and / or influence between variables is explained by multiple linear analysis techniques The results of this study indicate that leverage and guarantee have a significant effect, while firm size, profitability, activity, market value ratio, age, and trustee reputation have no significant effect on bond rating.Keywords: Bond Rating, Firm Size, Leverage, Profitability, Activity, Market Value Ratio, Age of Bond, Guarantee, Trustee Rreputation